(untitled) (REMUNOM, 2025)
This article is the result of research carried out in the Specialization Course in Autism Spectrum Disorder in the Field of Digital Technologies (TDICS), offered by the Federal University of Tocantins - UFT. Considering that digital resources provide and encourage different learning profiles by presenting the same content in different forms, such as audio, video and readings, research is carried out on multiple intelligences and mobile applications: connections and possibilities for learners with autism, in order to identify free and open mobile applications and the stimulation of the multiple intelligences of learners with autism. To this end, it is necessary to understand how these mobile applications stimulate multiple intelligences from the perspective of learners with autism, and to map the free and open applications found and the intelligence they stimulate and their suitability for learners with autism. A hypothetical deductive study is then carried out, with a qualitative and exploratory approach through bibliographic research and content analysis. In view of this, it is clear that technology present in everyday life should be seen as an ally, it is there to make life easier for learners with autism, helping them with their tasks and difficulties. Everyone learns, a child with autism may not be able to verbalize, but with the help of assistive technology they will be able to do so and develop their mental schemes, their intelligence, which leads to the realization that there are many free applications for learners with autism available in online stores and it is possible to find more than one software with the same function.